Alexander Randall may have had it right after all - Chi, Thomas; Taylor, Eric; Stoller, Marshall L. (Translational Andrology and Urology, 2014)
Several theories exist regarding the pathogenesis of urinary calculi, and the early incipient events leading to calculus formation remain the most controversial. The authors detail a theory by which microscopic Randall plaques (RP) lead to calcium oxalate calculi in idiopathic calcium oxalate stone formers (1).